A STUDY ON INCIPIENT TRENDS: THE REAL ESTATE SECTOR OF AHMEDABAD CITY (GUJARAT) - Shakilmiya, Malek; Farhana, Saiyed (International Journal of Research -GRANTHAALAYAH, 2017)
Risk is an exposure to potential loss or damage. It is a general tendency of people to obtain accurate prediction for the future plans of life, making them feel safe. In the real practice, though all matters are related to special laws however, the interaction and the balance between them is complex. This comes to the fact that the real estate’s development is complex and more risky and this may require knowledge and insight in order to professionalize the real estate development process. The complex conditions bring many uncertainties that make it difficult to judge for a perfectly correct prediction. It is therefore, we say that risk is everywhere and unavoidable. The paper highlights the annotations that are identified as the main problems and challenges of risk management in the Indian real estate companies to explore solutions for risk management in India and at last the literature review proceeds toward the highlights of Ahmedabad city of Gujarat state.